A Study on the Scope and Limit of International Exhaustion - SuCheol Kim (Journal of Intellectual Property)
Although Copyright Law includes provision for the exhaustion of distribution rights, other intellectual property laws do not explicitly address the exhaustion of rights. Nevertheless, most countries recognize the exhaustion theory of intellectual property rights as a general legal principle. International exhaustion, however, has been discussed separately for patents, trademarks, and copyrights. Given that these rights share strong similarities and serve the same fundamental purposes as intellectual property protections, distinguishing international exhaustion based on each type of right is theoretically and practically meaningless. In addition, considering modern trade trends—where many everyday products are simultaneously protected by patents, trademarks, and copyrights—and the growing significance of international trade, intellectual property rights should beintegrated manner when determining international exhaustion. This study examines the scope and limitations of international exhaustion theory from both subjective and objective perspectives. Specifically, it explores the extent to which intellectual property rights are subject to exhaustion and whether international exhaustion applies to products sold by a licensee in violation of contractual terms. Based on these considerations, I suggest a direction for the development of international exhaustion theory from an integrated intellectual property rights perspective.